ASSET RECOVERY DALAM TINDAK PIDANA KORUPSI MELALUI INSTRUMEN UNDANG-UNDANG TINDAK PIDANA PENCUCIAN UANG - Malto S. Datuan; Bismar Nasution; Mahmud Mulyadi; Mahmul Siregar (USU LAW JOURNAL, 2017)
ABSTRACT The development of the criminal offence of corruption in Indonesia keeps increasing and complex issue for law enforcement officers. As well as the number of countries that present financial losses, continue to increase from year to year. Eradication of corruption not only lies in prevention efforts as well as criminalization the corruptor, but also include actions asset recovery. The main issue raised in this research is how asset recovery in corruption through criminal recovery and civil recovery and how asset recovery through the instrument of money laundering legislation? This research is the juridical normative research, i.e. research which focused on reviewing the implementation of the norms or norms of positive law.The results showed that asset recovery through the criminal recovery or civil recovery in corruption has many drawbacks. The presence of the United Nations Convention Against Corruption (UNCAC) 2003 nor Act MLA (Mutual Legal Assistance) are not able to overcome barriers in asset recovery because it clashed with the political and legal systems in other countries. Civil forfeiture which has in rem have many advantages, but has not yet been adopted in Indonesia. Draft Legislations for Assets Recovery similar to the civil forfeiture of up to now has not been enacted. Whereas the provisions of asset recovery in Act of Money Laundering is more advanced than the Act of Corruption, due to more focus on follow the money rather than follow the suspect as well as discrete in personam i.e. part of criminal sanctions and also characterized the in rem i.e. in article 67 of Act No. 8 of 2010 on Prevention and Eradication of Money Laundering which allows it to seize the assets  are proceeds of crime without the results prove the fault of suspect, but a lawsuit intended to the assets (in rem) that will be deprived.   Keyword: Asset Recovery, corruption, money laundering